Cold flush after dynamic liver preservation protects against ischemic changes upon reperfusion – an experimental study. (10th October 2018) - von Horn, Charlotte; Hannaert, Patrick; Hauet, Thierry; Leuvenink, Henri; Paul, Andreas; Minor, Thomas; ,
Summary: Ex vivo machine perfusion of the liver after cold storage has found to be most effective if combined with controlled oxygenated rewarming up to (sub)‐normothermia. On disconnection of the warm graft from the machine, most surgeons usually perform a cold flush of the organ as protection against the second warm ischemia incurred upon implantation. Experimental evidence, however, is lacking and protective effect of deep hypothermia has been challenged for limited periods of liver ischemia in other models. A first systematic test was carried out on porcine livers, excised 30 min after cardiac arrest, subjected to 18 h of cold storage in UW and then machine perfused for 90 min with Aqix‐RSI solution. During machine perfusion, livers were gradually rewarmed up to 20 °C. One group ( n = 6) was then reflushed with 4 °C cold Belzer UW solution whereas the second group ( n = 6) remained without cold flush. All livers were exposed to 45 min warm ischemia at room temperature to simulate the surgical implantation period. Organ function was evaluated in an established reperfusion model using diluted autologous blood. Cold reflush after disconnection from the machine resulted in a significant increase in bile production upon blood reperfusion, along with a significant reduction in transaminases release alanine aminotransferase and of the intramitochondrial enzyme glutamate dehydrogenase. Interestingly, free radical‐mediated lipid peroxidation was also found significantly lower after cold reflush. No differences between the groups could be evidenced concerning histological injury and recovery of hepatic energy metabolism (tissue content of adenosine triphosphate). Post‐machine preservation cold reflush seems to be beneficial in this particular setting, even if the organs are warmed up only to 20 °C, without notion of adverse effects, and should therefore be implemented in the protocol.